2015
DOI: 10.1210/me.2014-1295
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic Activity of UCP1 in Human White Fat-Derived Beige Adipocytes

Abstract: Heat-producing beige/brite (brown-in-white) adipocytes in white adipose tissue have the potential to suppress metabolic disease in mice and hold great promise for the treatment of obesity and type 2 diabetes in humans. Here, we demonstrate that human adipose-derived stromal/progenitor cells (hASCs) from subcutaneous white adipose tissue can be efficiently converted into beige adipocytes. Upon pharmacological activation of peroxisome proliferator-activated receptor-γ, hASC-derived adipocytes activated beige fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 32 publications
6
69
0
Order By: Relevance
“…In conjunction with other studies (40,48,49) that includes work performed in primary adipocytes (50), our data strongly suggest Ubc9 inhibits PPAR␥ activity, resulting in repression of thermogenic target genes and oxidative metabolism, a finding that is unlikely conserved in 3T3-L1 cells (26). Although it is still unclear whether acquisition of brown fat features in human WAT is sufficient to affect energy expenditure, recent data suggests thermogenesis in human adipose-derived stromal cells is UCP1-dependent (51). Therefore, we propose disruption of Ubc9 expression promotes the thermogenic specificity of PPAR␥ transcriptional programs in human white adipocytes and thus may enhance the insulin-sensitizing effects of PPAR␥-activating drugs.…”
Section: Discussionsupporting
confidence: 83%
“…In conjunction with other studies (40,48,49) that includes work performed in primary adipocytes (50), our data strongly suggest Ubc9 inhibits PPAR␥ activity, resulting in repression of thermogenic target genes and oxidative metabolism, a finding that is unlikely conserved in 3T3-L1 cells (26). Although it is still unclear whether acquisition of brown fat features in human WAT is sufficient to affect energy expenditure, recent data suggests thermogenesis in human adipose-derived stromal cells is UCP1-dependent (51). Therefore, we propose disruption of Ubc9 expression promotes the thermogenic specificity of PPAR␥ transcriptional programs in human white adipocytes and thus may enhance the insulin-sensitizing effects of PPAR␥-activating drugs.…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that in addition to the supraclavicular area, thermogenic adipocytes also exist in human subcutaneous fat depots [8, 10]. We observed a clear activation of the thermogenic response and PKA signaling in differentiated hASCs isolated from subcutaneous fat depots (Fig.…”
Section: Resultssupporting
confidence: 63%
“…However, recent studies reported that stem cells from human WAT treated with the peroxisome proliferator-activated receptor-γ agonist rosiglitazone 79 or bone morphogenetic protein 7 80 easily differentiate toward beige adipocytes and markedly enhance oxygen consumption. In addition, bone morphogenetic protein 7-driven browning of adipocytes results in higher glucose and FA uptake than white adipocytes.…”
Section: Because [mentioning
confidence: 99%